1989
DOI: 10.1002/jemt.1060120206
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal movements during heterophagy and autophagy: With special reference to nematolysosome and wrapping lysosome

Abstract: Recent studies on lysosomal movements during heterophagy and autophagy performed in our laboratory for the past several years were reviewed; methods for the investigation of lysosomes and the cytoskeleton in these studies mainly involved electron microscopic cytochemistry. Lysosomal movements during heterophagy were observed in cultured rat alveolar macrophages taking up horseradish peroxidase (HRP) and rat peroxidase-antiperoxidase (PAP) by fluid-phase pinocytosis and adsorptive pinocytosis, respectively. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 100 publications
1
21
0
Order By: Relevance
“…Several studies highlight a range of findings including: (1) that lysosomes show microautophagy activity in vitro, which may be a mechanism for degradation of soluble cytoplasmic constituents in vivo, 51 (2) a lysosomal wrapping mechanism having features resembling those of microautophagy, 6,52 (3) changes in microautophagy apparently related to intrinsic alterations within cells (e.g., liver protein content, rates of protein synthesis and degradation, volumes of lysosomal-vacuolar components), 53 and (4) characterization of starvation-induced microautophagic vacuoles. 54 Glaumann and colleagues 51 showed that isolated rat liver lysosomes incubated with Percoll particles in vitro contain a number of vesicles, some of which contain (one or more) Percoll particles plus surrounding fluid.…”
Section: Microautophagy-mediated Degradation Pathways In Mammalian Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies highlight a range of findings including: (1) that lysosomes show microautophagy activity in vitro, which may be a mechanism for degradation of soluble cytoplasmic constituents in vivo, 51 (2) a lysosomal wrapping mechanism having features resembling those of microautophagy, 6,52 (3) changes in microautophagy apparently related to intrinsic alterations within cells (e.g., liver protein content, rates of protein synthesis and degradation, volumes of lysosomal-vacuolar components), 53 and (4) characterization of starvation-induced microautophagic vacuoles. 54 Glaumann and colleagues 51 showed that isolated rat liver lysosomes incubated with Percoll particles in vitro contain a number of vesicles, some of which contain (one or more) Percoll particles plus surrounding fluid.…”
Section: Microautophagy-mediated Degradation Pathways In Mammalian Cellsmentioning
confidence: 99%
“…6,52 The LWM was reported to occur in a variety of tissues under various (and notably mostly nonphysiological) conditions as follows: (1) the uptake and translocation of horseradish peroxidase in mouse histiocytes, which are component cells of the mononuclear phagocytic system, 6 (2) isolated hepatocytes after administration of glucagon or of cyclic AMP, 6 (3) Yoshida ascites cells treated with cortisone acetate in vitro or in vivo, 6 (4) splenic macrophages isolated from γ-ray-irradiated rats, 6 (5) mouse histiocytes after ovalbumin administration. 6 The common characteristics of LWM described in the above studies were as follows: (1) ATP is consumed as energy source for both sequestration of a particular cytoplasmic cargo and its subsequent degradation, (2) control of LWM is apparently mediated by actin filaments rather than by microtubules and (3) protein synthesis is necessary for LWM. 6,52 Using electron microscopy as the main detection technique, several forms of microautophagy-like sequestration structures have been described in mouse/rat liver hepatocytes.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the findings also indicate that the phagocytosis and intracellular processing of phagosomes in Sertoli cells could be stimulated by heating the testis, which had been reported causing injury of germ cells12), because an increasing of the number of lysosomes, particularly secondary lysosomes were observed in the cytoplasm. The fact that the nematolysosome was absent in the testicular cells indicates that nematolysosomes are not a ubiquitous structure of all the types of cells and tissues, although they have been found in several kinds of cells1-4, [10][11][13][14][16][17][18][19][20][21][22]. Meanwhile, in another study dealt with luteal cells (our unpublished data), the nematolysosomes were found to be increased in number after luteal cells naturally go to regressing.…”
Section: Discussionmentioning
confidence: 99%